Effects of sensory deprivation on glomerular interneurons in the mouse olfactory bulb: differences in mortality and phenotypic adjustment of dopaminergic neurons - Angelova, Alexandra; Tiveron, Marie-Catherine; Loizeau, Mathieu D.; Cremer, Harold; Platel, Jean-Claude (Frontiers in Cellular Neuroscience, 2023)
Neurogenesis persists in the mammalian subventricular zone after birth, producing various populations of olfactory bulb (OB) interneurons, including GABAergic and mixed dopaminergic/GABAergic (DA) neurons for the glomerular layer. While olfactory sensory activity is a major factor controlling the integration of new neurons, its impact on specific subtypes is not well understood. In this study we used genetic labeling of defined neuron subsets, in combination with reversible unilateral sensory deprivation and longitudinal in vivo imaging, to examine the behavior of postnatally born glomerular neurons. We find that a small fraction of GABAergic and of DA neurons die after 4 weeks of sensory deprivation while surviving DA-neurons exhibit a substantial decrease in tyrosine hydroxylase (TH) expression levels. Importantly, after reopening of the naris, cell death is arrested and TH levels go back to normal levels, indicating a specific adaptation to the level of sensory activity. We conclude that sensory deprivation induces adjustments in the population of glomerular neurons, involving both, cell death and adaptation of neurotransmitter use in specific neuron types. Our study highlights the dynamic nature of glomerular neurons in response to sensory deprivation and provide valuable insights into the plasticity and adaptability of the olfactory system.